Pemanfaatan Websocket dan EaselJS pada E-Marketplace Penjualan Mobil Bekas - Christiana, Wong Fanny; Andjarwirawan, Justinus; Dewi, Lily Puspa (Jurnal Infra, 2016)
Technology continues to grow from time to time. One of those technologies that still growing are web-socket and EaseIJS. Many people use these technologies to help website notification process. Those notifications are needed so that user can find out the latest news from a certain website. EaselJS is also one of the technologies that emerges in the field of canvas design.This website contains car sales that allows users to sell their cars throughout Indonesia without opening a physical showroom, as well as advertising in various places. The website provides complete information about the car being sold, from the interior and exterior.Based on test results, this website can run WebSocket function to provide latest ad, and EaselJS to edit the carâs interior pictures that will greatly help the guest to see the interior of a car in an image that has been edited.